Do as I Say, Not as I Do? Examining Possible Individual-Level Moderators in the Relationship Between Criminal Attitudes and Offending - Boccio, Cashen M. (Criminal justice and behavior, 2022)
Several criminological theories and numerous research studies suggest that criminal attitudes are related to delinquency and criminal behavior. In contrast, there is also an emerging body of literature that suggests that the behavior of many individuals is not consistent with their attitudes. This study addresses this contradiction in the literature by examining two possible individual-level moderators (i.e., self-control and depressive symptoms) that may explain why some adolescents may be involved in delinquent behavior when they report having attitudes disapproving of delinquency. The findings reveal that attitudes disapproving of delinquency are negatively associated with delinquent involvement; however, many respondents with attitudes of disapproving of delinquency still engaged in delinquent behavior. In addition, the findings suggest that self-control and depressive symptoms may moderate the association between attitudes disapproving of delinquency and delinquent involvement.